The effectiveness of pay-it-forward in addressing HPV vaccine delay and increasing uptake among 15-18-year-old adolescent girls compared to user-paid vaccination: a study protocol for a two-arm randomized controlled trial in China - Yifan Li; Chuanyu Qin; Shengyue Qiu; Yu He; Linchuan Pang; Xiaolan Xu; Vivian Wan-Cheong Yim; Shenglan Tang; Heng Du; Wenfeng Gong; Fan Yang; Joseph D. Tucker; et al. (BMC, 2023)
Abstract Background Human papillomavirus (HPV) vaccination could prevent cervical and other HPV-associated cancers attributable to vaccine-associated HPV types. However, HPV vaccination coverage among women aged 9-18 years old is low in China. Common barriers include poor financial affordability, minimal public engagement, and low confidence in domestically produced HPV vaccines. Pay-it-forward offers an individual a free or subsidized service then an opportunity to voluntarily donate and/or create a postcard message to support future people. This study aims to assess the effectiveness of pay-it-forward as compared to standard-of-care self-paid vaccination to improve HPV vaccine uptake among adolescent girls aged 15-18 years, who are left out in the current pilot free HPV vaccination task force in some parts of China. Methods This is a two-arm randomized controlled trial in Chengdu, China. Eligible adolescent girls (via caregivers) will be randomly selected and recruited through four community health centers (one in the most developed urban areas, one in higher middle-income and one in lower middle-income suburban areas, and one in the least developed rural areas) using the resident registration list. A total of 320 participants will be randomized into two study arms (user-paid versus pay-it-forward vaccination) in a 1:1 ratio. The intervention assignment will be blinded to recruiters and participants using envelop concealment until the research assistants open the envelop to determine which treatment to deliver to each individual. The primary outcome of the study will be HPV vaccine uptake by administrative data. Secondary outcomes include costs, vaccine hesitancy, and the completion rates of the 3-dose HPV vaccination series. Discussion This study will investigate an innovative pay-it-forward strategy's effectiveness and economic costs to improve HPV vaccination among 15-18-year-old adolescent girls. Study findings will have implications for increasing HPV vaccine uptake in places where HPV vaccines are provided for a fee. Trial registration Chinese Clinical Trial Registry (ChiCTR), ChiCTR2200055542. Registered on 11 January 2022. Graphical Abstract